Alliance orientation, total quality management and performance of Nigerian public universities: The role of corporate entrepreneurship - Aliyu, Mukhtar Shehu (2016)
The study aims to investigate an association between alliance orientation and total quality management on the performance of Nigerian public universities, with the moderating variable of corporate entrepreneurship. Literature was reviewed in management and other related fields for better understanding of past, present and future needs in the study area. Higher education is a vital tool for the economic growth in Nigeria and it constitutes an important basis of producing high level manpower which significantly contributes towards the economic development of the country. As a result of a thorough review of literature, a model was proposed to examine these associations. A questionnaire survey design was used and the academic leaders of 13 public Northwestern Nigerian Universities were the respondents. The study employed systematic sampling technique in data collection, and 434 usable questionnaires were received from the respondents. A combination of descriptive and inferential statistics was used to analyze the data collected using SPSS statistical package version 20, and smart partial least squares (PLS) 2.0 M3. The findings of this study indicate thatalliance orientation and total quality management have direct significant positive relationship with performance, whereas, corporate entrepreneurship was found to moderate on the relationship between alliance orientation, total quality management and performance among Nigerian public Universities. Finally, study implications for theory and practice, limitations, conclusions as well as direction for future research were provided and discussed